Influence of Non-Integer Harmonics and Interference on SAPF - Zhang Chao; Ren Zi-Hui; Zhang Yi-Jun; Ma Xiao-Ping (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Inter-harmonics and non-periodic disturbance generated by aging SAPF or other reasons would impact SAPF performance. In this paper, three-level SAPF was used as example: the mathematical model of three-level SAPF under the definition of virtual flux was built. The power theory under the definition of CPT was discussed. Based on the definition of CPT, the method for SAPF detection system with CPT was studied and the performance was verified by comparing results with the PQ theory. Repetitive control and PI control were used as a combination system for grid inter-harmonics compensation. EID controller was used to improve the performance of repetitive controller for inter-harmonics and non-periodic disturbance rejection. Finally, system reliability was verified by MATLAB simulation and three-level experiment platform. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4443